Factors that hinder academic productivity among University of the Philippines in the Visayas College of Management students - Altamia, Michael T.; Diaz, Voltaire G.; Enabore, Mary Rosalyn T.; Valla, Joy J. (1997.)
This study is aimed at determining the factors behind the sloppy academic performance of UPV-CM students. Specifically, the study is focused on : (1) The major factors that affect productivity among UPV-CM students ; (2) The behaviour of students relative to their academic productivity ; (3) different views regarding productivity improvement. Data were gathered, at random, from UPV-CM students using a 23 item questionnaire. The questions posed by the later are basically categorized into six (6) factors, namely: SCHOOL, TEACHER, GEOGRAPHY, STUDENTS, PEER, AND FAMILY. The statistical tool used in the study was percentage. The conclusion of the study was that the six factors aforementioned greatly affect the productivity of UPV-CM students. In this regard, recommendations concerning possible changes in students' academic productivity are available.
Research Paper (Mgt 200-Management Research) -- Iloilo City : University of the Philippines in the Visayas-College of Management, March 24,1997.